208 Evaluation of the Standardized Ileal Digestible Total Sulfur Amino Acid:Lysine Requirement for 14-27 Kg PIC Nursery Pigs. (10th April 2018) - Graham, A; Knopf, B; Goncalves, M A D; Orlando, U A D; Greiner, L
Abstract: One thousand two hundred PIC (337 × Camborough; PIC, Hendersonville, TN) barrows and gilts were used to further evaluate the Standardized Ileal Digestible (SID) total sulfur amino acid (TSAA) ratio relative to lysine requirement in 14-27.5 kg nursery pigs. Prior to the start of the study, pigs were fed a basal diet that contained 1.45% SID lysine for one week. At the start of the study, the pigs averaged 14.0 kg. The lightest 10% of pigs were sorted off to form one replication and the remaining pigs were sorted by gender and placed into blocks with 25 pigs per pen. Blocks were set for the 5 treatments (52.0, 56.5, 61.0, 65.5, 70.0 SID TSAA:Lys) within gender of similar weights with the block. The diets consisted of corn, soybean meal and dried distiller's grains and were balanced for the amino acids with the inclusion of feed grade amino acids. Standardized ileal digestible (SID) lysine level was 1.15% across all diets with the SID Met+Cys increasing from 0.60 to 0.80%, respectively. All other nutrients met or exceeded the NRC (2012) recommendations. Pen weights and feed intake information were collected at the start and end of the phase to allow for calculation of ADG, ADFI, and G:F. The pigs were porcine reproductive respiratory syndrome and porcine epidemic diarrhea virus negative. Data were analyzed as a randomized complete block design using the PROC MIXED procedure of SAS with pen as the experimental unit and treatment as a fixed effect and block as the random effect. There were 9 replications of pen per treatment group. Results were considered significant at P ≤ 0.05 and considered a trend at P > 0.05 and P ≤ 0.10. As the SID TSAA:Lys ratio was increased from 52-70, there were no statistically significant differences in ADG (0.633, 0.639, 0.646, 0.633, and 0.652 kg/d) or in G:F (0.61, 0.63, 0.62, 0.63, and 0.62). There was a quadratic tendency for improvement in G:F as the ratio increased. In conclusion, this study did not demonstrate a significant difference in performance across the SID TSAA:Lys treatments only a tendency for feed conversion improvement.